Gelation landscape engineering using a multi-reaction supramolecular hydrogelator system - Foster, Jamie S.; Zurek, Justyna M.; Almeida, Nuno M. S.; Hendriksen, Wouter E.; le Sage, Vincent A. A.; Lakshminarayanan, Vasudevan; Thompson, Amber L.; Banerjee, Rahul; Eelkema, Rienk; Mulvana, Helen; Paterson, Martin J.; van Esch, Jan H.; et al. (Journal of the American Chemical Society, 2015)
Simultaneous control of the kinetics and thermodynamics of two different types of covalent chemistry allows pathway selectivity in the formation of hydrogelating molecules from a complex reaction network. This can lead to a range of hydrogel materials with vastly different properties, starting from a set of simple starting compounds and reaction conditions. Chemical reaction between a trialdehyde and the tuberculosis drug isoniazid can form one, two, or three hydrazone connectivity products, meaning kinetic gelation pathways can be addressed. Simultaneously, thermodynamics control the formation of either a keto or an enol tautomer of the products, again resulting in vastly different materials. Overall, this shows that careful navigation of a reaction landscape using both kinetic and thermodynamic selectivity can be used to control material selection from a complex reaction network.

Gadolinium(III)-based porous luminescent metal-organic frameworks for bimodal imaging - Kundu, Tanay; Mitra, Shouvik; Diaz Diaz, David; Banerjee, Rahul (Chempluschem, 2016)
Gd-III-based metal-organic frameworks, Gd-pDBI-1 and Gd-pDBI-2, have been synthesized using the linker pDBI (pDBI=1,4-bis(5-carboxy-1H-benzimidazole-2yl)benzene). They exhibited structural diversity due to subtle change in reaction constituents. Owing to the judicious choice of the fluorescent linker, the materials could be used for bimodal imaging (fluorescent and magnetic resonance) and displayed a modest T1 relaxivity value.